Learning Curve for Retroperitoneoscopic Renal Pedicle Lymphatic Disconnection for Intractable Chyluria: A Single Surgeon’s Experience - Wang, Long; Ou, Zhenyu; Chen, Hequn; Cao, Zhenzhen; Tang, Zhengyan; Chen, Xiang; Zu, Xiongbing; Liu, Longfei; Qi, Lin (Urology Journal, 2012)
PURPOSE: To evaluate the surgical experience and outcomes of retroperitoneoscopic renal pedicle lymphatic disconnection (RRPLD) and to define a learning curve for this minimally invasive technique to treat patients with intractable chyluria. MATERIALS AND METHODS: We collected the clinical records of 40 consecutive patients who were selected for RRPLD of 42 renoureteral units between 2007 and 2010 for chyluria by a single surgeon with no experience for this procedure. Patients’ demographics and peri-operative parameters were recorded and compared. Operation time, blood loss, and other peri-operative parameters were analyzed to document the learning curve for the procedure. RESULTS: All the 40 patients, 14 women and 26 men, underwent RRPLD successfully, and no open conversions were needed. The median operation time was 77.5 minutes [interquartile ranges (IQR): 69.0 to 89.0] and the median blood loss was 46.5 mL (IQR: 35.0 to 67.0). A total of five complications occurred (11.9%). We divided the patient cohort to the first 20 (group 1) and the last 20 (group 2) patients since operation time reached a plateau after about 20 cases. There were significant differences in the operation time (P = .000) and the blood loss (P = .006) between the two groups. The two phases did not differ in terms of demographic data, peri-operative complications, gastrointestinal recovery time, extubation time, or hospitalization duration. CONCLUSION: Retroperitoneoscopic renal pedicle lymphatic disconnection is a well standardized and reproducible procedure. This study of the learning curve of a single surgeon suggests that competence at performing RRPLD is reached after approximately 20 cases.